Peripheral Blood Mononuclear Cells Infiltration Downregulates Decidual FAAH Activity in an LPS‐Induced Embryo Resorption Model. Issue 6 (10th November 2016) - Wolfson, Manuel Luis; Aisemberg, Julieta; Correa, Fernando; Franchi, Ana María
Abstract : Maternal infections with gram‐negative bacteria are associated with miscarriage and are one of the most common complications during pregnancy. Previous studies from our group have shown that lipopolysaccharide (LPS)‐activated infiltrating peripheral blood mononuclear cells (PBMC) into decidual tissue plays an important role in the establishment of a local inflammatory process that results in embryo cytotoxicity and early embryo resorption. Moreover, we have also shown that an increased endocannabinoid tone mediates LPS‐induced deleterious effects during early pregnancy loss. Here, we sought to investigate whether the infiltrating PBMC modulates the decidual endocannabinoid tone and the molecular mechanisms involved. PBMC isolated from 7‐day pregnant mice subjected to different treatments were co‐cultured in a transwell system with decidual tissue from control 7‐day pregnant mice. Decidual fatty acid amide hydrolase (FAAH) activity was measured by radioconvertion, total decidual protein nitration by Western blot (WB), and decidual FAAH nitration by immunoprecipitation followed by WB. We found that co‐culture of PBMC obtained from LPS‐treated mice increased the level of nitration of decidual FAAH, which resulted in a negative modulation of decidual FAAH activity. Interestingly, co‐treatment with progesterone or aminoguanidine prevented this effect. We found that LPS‐treated PBMC release high amounts of nitric oxide (NO) which causes tyrosine nitration of decidual FAAH, diminishing its enzymatic activity. Inactivation of FAAH, the main degrading enzyme of anandamide and similar endocannabinoids, could lead to an increased decidual endocannabinoid tone with embryotoxic effects. J. Cell. Physiol. 232: 1441–1447, 2017. © 2016 Wiley Periodicals, Inc. Abstract : PBMC release a soluble factor which modulates the decidual FAAH activity. Peroxynitrite participates in LPS‐treated PBMC decidual FAAH activity modulation. PBMC from LPS‐treated mice increased the nitration levels of decidual FAAH which resulted in a decreased enzymatic activity.